Academic computing components in Malaysian Higher Education - Mokhtar, Shamsul Anuar; Alias, Rose Alinda (2005)
In the information age, higher education institutions in Malaysia are implementing academic computing to provide better education services and remain competitive in a global knowledge industry. It encompasses the utilisation of staff, infrastructure (hardware and software) and services (technology, information content and human resources) which enable and support the management and delivery of academic programmes in teaching, learning and research. Research by UNESCO (2004) shows that many Asia-Pacific countries including Malaysia lack the proper framework to assess and evaluate IT implementation in higher education. Seven main areas of academic computing are identified. They include teaching and learning, research and publication, infrastructure, information services, institutional support, plan and policy and assessment. These areas encompass a total of thirty-four components. To determine the importance of these components within the Malaysian context, a pilot survey was conducted on a selected higher education institution. This research discusses the results.